Database modelling for vision impaired indoor navigation systems: Extended abstract - Jayakody, J.; Murray, Iain; Herrmann, J. (2016)
Cooperative research has been conducted to improve navigation services for vision impaired when they are moving through an indoor environment. Hence, to facilitate vision impaired individual in indoor environment requires a formal modelling approach for map generation and decision making about navigation pathways avoiding obstacles. The proposed data model consists "AccessBIM" database (DB) and API functions. The "AccessBIM" features such as, database connection initiation, function call, function return and database connection termination are organized as a series of function objects that meet the various needs of the database to maintain the relational schema. The proposed API primarily consists of two components, namely; DB connector and the API functions. Proposed "AccessBIM" DB will be implemented using real-time database such as "PostgreSQL". The weighted focus will be given to the areas such as Queries, Indexes and Transactions in relation to tuning the DB and the queries. The performance of the proposed API will be evaluated based on the time required to parse and Data insert rate and retrieval rates.